An overview of cetacean stranding around Hainan Island in the South China Sea, 1978–2016: Implications for research, conservation and management. (March 2019) - Liu, Mingming; Lin, Mingli; Zhang, Peijun; Xue, Tianfei; Li, Songhai
Abstract: The South China Sea (SCS) is known to support diverse cetacean species, yet their stranding information has not been well documented. To fill this knowledge gap, available records on cetacean stranding around Hainan Island in the SCS from 1978 to 2016 were collected and overviewed. In total, 112 records were obtained. Among them, 19 records involved 19 baleen whales (5 mysticeti species) and 93 records involved 134 toothed whales (12 odontoceti species). More stranding events occurred in the waters along the east coast than in the waters along the west coast, which was especially true for toothed whales stranding events. This may reflect the distribution patterns of cetaceans around Hainan Island. The spatial distribution of stranding events might be driven by different oceanographic features between the east and west offshore waters of the Hainan Island. The number of stranding events increased gradually from 1978 to 2000 and more rapidly from 2000 to 2016, which is likely due to both increasing public attentions and increasing anthropogenic activities within the SCS in recent decades. Stranding events were recorded throughout the year but peaked in spring ( p = 0.016). In sum, cetacean stranding events occurred rather frequently around Hainan Island. The establishment of a regional stranding network in the SCS is conducive for further research, conservation and management of cetaceans in this region. More scientific data about the survival status of cetaceans and threats to them in the SCS are also needed. Highlights: Cetacean stranding records around Hainan were overviewed. Species composition and spatial-temporal pattern was analyzed. Regional cetacean stranding networks were emphasized.